Reward- and Punishment-Sensitive Relational Mechanisms: Gender Asymmetries in Dyadic Coping and Relationship Satisfaction - FERENCZI, Andrea; MÉSZÁROS, Veronika (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
THEORETICAL BACKGROUND – Relationship satisfaction is not merely an individual experience but a phenomenon that emerges through partners’ interactions, in which the coping behaviours of both individuals play a crucial role. GOALS – The present study aimed to explore how different dimensions of dyadic coping are associated with relationship satisfaction through intrapersonal (actor) and interpersonal (partner) effects, and whether these associations exhibit gender asymmetry. METHODS – The sample consisted of 184 heterosexual couples (N = 368; 184 women and 184 men). Women’s ages ranged from 18 to 75 years (M = 32.94, SD = 12.78), while men’s ages were between 18 and 85 years (M = 35.62, SD = 13.50). Dyadic coping was assessed using relevant subscales of the Dyadic Coping Inventory (DCI-H), and relationship satisfaction was measured with the Hungarian version of the Relationship Assessment Scale (RAS-H). The hypotheses were tested within the Actor–Partner Interdependence Model (APIM) using structural equation modeling. RESULTS – The results showed that for both men and women, positive forms of dyadic coping were positively associated with individuals’ own relationship satisfaction, whereas negative coping was negatively associated with the same. Common dyadic coping and its positive evaluation were significantly related to the satisfaction of both partners. With regard to partner effects, a gender asymmetry emerged: men’s positive coping was more strongly associated with their female partners’ relationship satisfaction, whereas negative coping was particularly strongly related to men’s own satisfaction. These findings may reflect differentiated functioning of reward- and punishment-sensitive relational mechanisms: women’s relationship satisfaction appears to be more responsive to reinforcing and validating interactions, whereas men’s satisfaction seems to be more strongly affected by critical and rejecting behaviours. CONCLUSIONS – The study contributes to a deeper understanding of gender-specific patterns in dyadic coping and offers practical implications for the targeted design of dyadically oriented couple therapy interventions.